2011
DOI: 10.1111/j.1740-8709.2011.00354.x
|View full text |Cite
|
Sign up to set email alerts
|

Legislation should support optimal breastfeeding practices and access to low‐cost, high‐quality complementary foods: Indonesia provides a case study

Abstract: It is important to support women to exclusively breastfeed for 6 months and continue breastfeeding for 24 months and beyond. It is also necessary to provide the poor with access to affordable ways to improve the quality of complementary foods. Currently, many countries do not have the legal and policy environment necessary to support exclusive and continued breastfeeding. Legislative and policy changes are also necessary for introducing complementary food supplements, allowing them to be marketed to those who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 15 publications
0
21
0
1
Order By: Relevance
“…Slowly, global policy frameworks are being built to support MNP supply. For example, to address regulatory challenges, global efforts are underway to provide specific guidance on MNP labelling in the National Codex Alimentarius (CODEX, ; Soekarjo & Zehner, ; Zlotkin, Siekmann, Lartey, & Yang, ), to mitigate the inappropriate promotion of foods for infants and young children (WHO, ). This may help ease MNP classification issues in the long term, and in the meantime, countries can refer to Home Fortification Technical Advisory Group tools to help ensure that local MNP marketing does not violate the Code for the Marketing of Breastmilk Substitutes (HF‐TAG, ).…”
Section: Discussionmentioning
confidence: 99%
“…Slowly, global policy frameworks are being built to support MNP supply. For example, to address regulatory challenges, global efforts are underway to provide specific guidance on MNP labelling in the National Codex Alimentarius (CODEX, ; Soekarjo & Zehner, ; Zlotkin, Siekmann, Lartey, & Yang, ), to mitigate the inappropriate promotion of foods for infants and young children (WHO, ). This may help ease MNP classification issues in the long term, and in the meantime, countries can refer to Home Fortification Technical Advisory Group tools to help ensure that local MNP marketing does not violate the Code for the Marketing of Breastmilk Substitutes (HF‐TAG, ).…”
Section: Discussionmentioning
confidence: 99%
“…Different nations have various rules for introducing a new category of products. As shown in Indonesia (Soekarjo & Zehner 2011) and Kenya (CJ Jones, personal communication), a new standard for CFSs is required for initiating a market‐based project. In Bangladesh, government authorities did not allow promotion of Monimix, an MNP, through mass media when the product was first introduced through social marketing, which affected the volume of sales (Mr Mahbubur Rahman, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…Young infants thrive best when exclusively breastfed for the first 6 months of life and after that, a prompt and proper complementary foods need to be introduced in addition to continued breastfeeding in order to fully meet their nutrient requirements for optimal growth (WHO and UNICEF, 2003;Soekarjo & Zehner, 2011). Previous studies have shown that proper combination, processing and blending of certain cereals and legumes have the potential to provide nutrients and serve as complementary food for infants (Fernandez et al, 2002;Solomon, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Fortified commercial complementary foods are unavailable in rural areas and where available are usually expensive beyond the reach of most families in rural areas especially in Nigeria (Ikujenlola, 2014). Furthermore, rather than replacing the local foods or requiring the low income mothers to buy the expensive commercially available fortified weaning/complementary diet correct combination/formulation of their locally cultivated cereals and legumes that are readily available to the family can be a feasible approach to addressing the nutritional requirements of these infants since 90% of the people living in the northern region of Nigeria rely on crop cultivation as their primary source of livelihood (Soekarjo & Zehner, 2011). (FAO/WHO/UNICEF, 1971) has emphasized the use of local foods formulation should be guided by the following principles: (i) high nutritional quality to supplement breastfeeding (ii) acceptability (iii) low price (iv) use of local food item (Dewey and Brown, 2003).…”
Section: Introductionmentioning
confidence: 99%